Japanese quails (Coturnix Japonica) show keel bone damage during the laying period—a radiography study - Hildebrand, Lisa; Gerloff, Christoph; Winkler, Birthe; Eusemann, Beryl Katharina; Kemper, Nicole; Petow, Stefanie (Frontiers in Physiology, 2024)
Keel bone damage is an important welfare issue in laying hens and can occur with a high prevalence of up to 100 % of hens within one flock. Affected hens suffer from pain. Although multiple factors contribute to the prevalence and severity of keel bone damage, selection for high laying performance appears to play a key role. With up to 300 eggs/year, Japanese quails show a high laying performance, too, and, thus, may also show keel bone damage. However, to our knowledge, there are no scientific results on keel bone damage in Japanese quails to date. This could indicate a general loss of bone substance and/or demineralization of the keel bone. Our study shows that keel bone damage is not only a problem in laying hens but also affects female Japanese quails. Therefore, the aim of this study was to assess whether keel bone fractures and deviations occur in Japanese quails and to obtain more detailed information about the development of their keel bone during the production cycle.A group of 51 female quails were radiographed at 8, 10, 15, 19, and 23 weeks of age. The X-rays were used to detect fractures and deviations and to measure the lateral surface area, length, and radiographic density of the keel bone. In addition, the length of the caudal cartilaginous part of the keel bone was measured to learn more about the progress of ossification. At 23 weeks of age, quails were euthanized and their macerated keel bones assessed for fractures and deviations. Both keel bone deviations and keel bone fractures were detected in the Japanese quails. In the 23 rd week of age, 82% of the quails had a deviated keel bone as assessed after maceration. Furthermore, there was a decrease in radiographic density, lateral surface area, and length of the keel bone between weeks of age 8 and 19.